ISLAM, KORUPSI DAN GOOD GOVERNANCE DI NEGARA-NEGARA ISLAM - Umam, Ahmad Khoirul (Al-Ahkam, 2014)
The revitalization of religion function —that some people think— is an effective instrument to fight the cancer of corruption and also the implementation of democratization and liberalization of the market. Value systems, moral teachings and spirituality in religion are considered to be opposite of the corruption characters growing in the contemporary society. The more religiosity of a society leads to the expectation for the lower corruption. However, according to the Corruption Perception Index (CPI) data, we will exactly find a tendency of paradoxical phenomena. For example, in the context of Islamic countries, the high of influence for the Muslims belief to their religion is not directly proportional to the commitment of the corruption eradication in the Muslim populized countries mostly. This phenomenon deserves to be shared reflection, to find the answers of classic questions; why does corruption tend becoming habit of Muslim community who are uphold moral principles and integrity in social life and state? It causes this article to discuss the relationship between religion and corruption in general, and also to elaborate it by dealing with the experience of Islamic countries